Individual and Simultaneous Electrochemical Detection of Bisphenol A and Bisphenol S in Food Samples Using Triethylenetetramine Functionalized Multi-Walled Carbon Nanotubes - KÖK YETİMOĞLU, ECE (My University, 2022)
In this concept, multi-walled carbon nanotubes (MWCNTs) were functionalized by triethylenetetramine (TETA-MWCNTs), and the as-synthesized TETA-MWCNT materials were utilized for the simultaneous voltammetric detection of bisphenol A (BPA) and bisphenol S (BPS). The voltammetric behaviors were tested by cyclic voltammetry (CV) and square-wave voltammetry (SWV). The high-priority experimental parameters have been carefully optimized. The designed sensor exhibited exceptional electrocatalytic activity toward the oxidation of BPA and BPS and provided two well-separate oxidation peaks enough to quantify BPA and BPS in a binary mixture. The standard curve was linear over the concentration range of 1.0–30 μM for both analytes. The detection limit was estimated to be 0.35 μM and 0.56 μM for BPA and BPS, respectively.
Keywords: Tarımsal Bilimler; Ziraat; Gıda Mühendisliği; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Food Engineering; Engineering and Technology; GIDA BİLİMİ VE TEKNOLOJİSİ; Tarım Bilimleri; Tarım ve Çevre Bilimleri (AGE); FOOD SCIENCE & TECHNOLOGY; AGRICULTURAL SCIENCES; Agriculture & Environment Sciences (AGE); Yemek bilimi; Yaşam Bilimleri; Food Science; Life Sciences; Bisphenol A; Bisphenol S; Electrochemical sensor; Triethylenetetramine; Carbon nanotubes; Food analysis; METAL-ORGANIC FRAMEWORK; SELECTIVE DETECTION; MODIFIED ELECTRODE; SENSING PLATFORM; HUMAN URINE; SENSOR; WATER; MICROEXTRACTION; Bisphenol A; Bisphenol S; Electrochemical sensor; Triethylenetetramine; Carbon nanotubes; Food analysis